1986
DOI: 10.1104/pp.82.3.834
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Responses of Leaves to Water Stress, Expressed by Photoacoustics and Related Methods

Abstract: The effect of rapid dehydration of detached tobacco leaves (Nicotiana tabacum L.) on the photochemical apparatus of photosynthesis was studied in vivo by a combination of methods: photoacoustics, chlorophyll a fluorescence, and cytochrome fdifference spectroscopy. It was shown that the inhibition of gross 02 evolution was mainly caused by inactivation of PSII: (a) The saturation curve of cytochrome-fphotooxidation by farred (>710 nanometers) light was resistant to the stress, leading to the conclusion that pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 13 publications
(21 reference statements)
0
7
0
1
Order By: Relevance
“…Their chloroplast structure and composition and the photochemical reactions, particularly PS II activity, have been shown to be directly affected. The harmful effects of severe dehydration were manifested in considerable changes of electron transport capacity and in reduction of O 2 evolution (Govindjee et al, 1981;Havaux et al, 1986;Chen and Hsu, 1995;He et al, 1995), but the primary target of PS II drought inhibition is still controversial. Damage to electron donation from the water oxidizing system (Canaani et al, 1986), considerable depletion of the PS II core and structural reorganisation of the remaining centres (Giardi et al, 1996), changes in PS II membrane protein metabolism (He et al, 1995), and inhibition of both the oxygen-evolving complex and the acceptor side of PS II (Skotnica et al, 2000) have been considered as some possible reasons for PS II impairment in water-stressed plants.…”
Section: Introductionmentioning
confidence: 99%
“…Their chloroplast structure and composition and the photochemical reactions, particularly PS II activity, have been shown to be directly affected. The harmful effects of severe dehydration were manifested in considerable changes of electron transport capacity and in reduction of O 2 evolution (Govindjee et al, 1981;Havaux et al, 1986;Chen and Hsu, 1995;He et al, 1995), but the primary target of PS II drought inhibition is still controversial. Damage to electron donation from the water oxidizing system (Canaani et al, 1986), considerable depletion of the PS II core and structural reorganisation of the remaining centres (Giardi et al, 1996), changes in PS II membrane protein metabolism (He et al, 1995), and inhibition of both the oxygen-evolving complex and the acceptor side of PS II (Skotnica et al, 2000) have been considered as some possible reasons for PS II impairment in water-stressed plants.…”
Section: Introductionmentioning
confidence: 99%
“…We have generally observed that under many different stress conditions there is no obligatory linear relation between the inhibition of oxygen evolution and energy storage. Energy storage is usually much less sensitive to many stresses than oxygen evolution (4,10). Energy storage reflects total photoactivity, including those photoactivities that are not related directly to oxygen evolution.…”
Section: Effect Of Exposure To High Fluence Rates On Oxygen Evolutionmentioning
confidence: 99%
“…While these 3 phases have not been recognized before, they could easily be superimposed on some data sets that compared F v /F m with environmental variables (e.g. Havaux et al 1986a; Larcher et al 1990), while the middle phase seems to be missing from some (e.g. Epron and Dreyer 1992; Boorse et al 1998) and the third phase was not reached by others (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…4), indicating that TLP has no physiological significance in setting the limits of overall UWC. We chose WC at F c as setting the preferred lowest limit of utilizable water on grounds that (a) it is sharply defined; (b) it loosely corresponded to the critical F v /F m used for setting the limits to chilling and heat tolerance in other studies ( Larcher et al 1990, <0.7; Boorse et al 1998, 50% drop in activity); (c) it does not exceed the limits at which full photochemical recovery is possible ( Havaux et al 1986a,b; Valladares and Pearcy 1997; de Mattos et al 1999, <0.65); (d) it corresponded to a RWC for our most sclerophyllous species (29%), similar to the point (25% RWC) at which the Mediterranean oak, Quercus petraea , first showed a significant effect of water stress on F v /F m , representing the final stage of ‘dehydration‐induced dysfunctions in photosynthesis’ ( Epron and Dreyer 1992); and (e) it was very close to B, representing the theoretical limit of water availability.…”
Section: Discussionmentioning
confidence: 99%